Global class Japanese SMEs - Kurosaki, Makoto 1944- (Japan library (Shuppan Bunka Sangyo Shinko Zaidan))
"Thirty years have passed since Japan emerged on the global stage as the second largest economy quickly moving upwards. More than twenty years have passed since the bubble burst, wiping away inflated dreams of Japan as Number One. The Cold War ended and China has overtaken Japan as Number Two. The digital revolution has come and IoT is changing everything. And yet Japan remains near the top as the third richest economy in the world despite the fallout from the scandals and disappointing performance from some of Japan's former giants"--Back cover.